A enfermagem frente à detecção precoce da sepse na unidade de terapia intensiva: uma revisão integrativa de literatura - MESQUITA, Isabela Araújo de (2020)
Sepsis means a complex clinical condition, characterized by the presence of life-threatening organic dysfunction, due to the host's deregulated response to infection. Moreover, it has a high incidence, with high costs, being the main cause’s mortality in Intensive Care Units of public and private hospitals. In this context, their early recognition and appropriate curing are key factors in changing this scenario. That way, this research aims to discuss the role of nursing in the early identification of sepsis in the Intensive Care Unit environment, through scientific research produced in the period from 2010 to 2019. About the methodological point of view, it is an Integrative Literature Review (RIL), with a qualitative approach, from 2010 to 2019, in the databases BDENF, LILACS and MEDLINE available in the virtual health library (VHL). Of the most relevant results, 8 publications were analyzed for the sample, corresponding to 5 publications found in the LILACS database and 3 publications found in the BDENF database. Among the themes discussed if approached: Nurses' understanding about the importance of early sepsis identification; Nurse´s knowledge about actions in the early sepsis identification; Facilities and difficulties encountered by the nurse in the early identification and, finally, the main strategies used for the early sepsis identification on the intensive care units. It has considered a shortage of studies on the subject studied. Is also observed by that nurses understand their importance in this scenario; however, there is a knowledge gap of nurses regarding the effective recognition of clinical signs of septic patients and evolution to its most severe form as well as in the difficulty of access to information. In addition, it has identified that nurse´s actions against early detection have focused mainly on vital signs checking and bedside monitoring of possible manifestations of organic dysfunction. In relation to the main facilitating strategies in this process, the mobile technologies used as a facilitator in the early recognition and improvement of patient care are highlighted, as well as the reduction of human errors and contributing to the learning of nursing professionals. Thus, encouragement to the development of continuing education programs regarding sepsis, as well as the relevance of the nurse in the management of this disease and the use of protocols to optimize the service in the UTI, are encouraged, providing positive results in the future.